2021
DOI: 10.3389/fpubh.2021.570147
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of COVID-19 Admissions in the New York City Public Health System and Variations by Hospitals and Boroughs During the Initial Pandemic Response

Abstract: Introduction: In the initial pandemic regional differences may have existed in COVID-19 hospitalizations and patient outcomes in New York City. Whether these patterns were present in public hospitals is unknown. The aim of this brief study was to investigate COVID-19 hospitalizations and outcomes in the public health system during the initial pandemic response.Methods: A retrospective review was conducted on COVID-19 admissions in New York City public hospitals during the exponential phase of the pandemic. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…They found large heterogeneity with higher hospitalization rates in the initial epicenter. Similar results for the first wave were found in Aleta et al BMC Medical Research Methodology (2023) 23:24 Italy [33], Saudi Arabia [34], Scotland [35] or New York City [36]. In terms of LoS, an early systematic review conducted in April 2020 found a median of 14 days in China and 5 days in the rest of the world [37].…”
Section: Introductionsupporting
confidence: 73%
“…They found large heterogeneity with higher hospitalization rates in the initial epicenter. Similar results for the first wave were found in Aleta et al BMC Medical Research Methodology (2023) 23:24 Italy [33], Saudi Arabia [34], Scotland [35] or New York City [36]. In terms of LoS, an early systematic review conducted in April 2020 found a median of 14 days in China and 5 days in the rest of the world [37].…”
Section: Introductionsupporting
confidence: 73%
“…Facing tremendous surge conditions, hospitals across the city assembled teams for the purpose of organizing, updating and redirecting clinical and logistical efforts day‐to‐day. These varied greatly between institutions; some of the variation reflected socioeconomic differences between healthcare systems and even individual sites 17–19 . Some municipal hospitals lacked the ability to make platforms for virtual meetings routinely available to clinical departments or individuals.…”
Section: Inceptionmentioning
confidence: 99%
“…These varied greatly between institutions; some of the variation reflected socioeconomic differences between healthcare systems and even individual sites. [17][18][19] Some municipal hospitals lacked the ability to make platforms for virtual meetings routinely available to clinical departments or individuals. In one such case, the emergency room became a venue for in-person interdepartmental and multidisciplinary meetings at each change of shift.…”
Section: Reflectionmentioning
confidence: 99%
“…Brant et al [200], 2021; Dhar et al [201], 2019; Egede et al [202], 2021; Kukhareva et al [203], 2022; Mahajan et al [204], 2022; Manzar [205], 2022; McCarthy et al [206], 2021; Mehta et al [207], 2018; Nasehi et al [208], 2018; Patil et al [209], 2022; Reddy et al [210], 2021; Renjithlal et al [211], 2022; Torres et al [212], 2023 Adult Dinesh et al [213], 2021; Harbison and Gillan [214], 2018; Khanna et al [215], 2021; McCain et al [216], 2022; Rajamani et al [217], 2015; Simmons et al [218], 2022…”
Section: Population Healthmentioning
confidence: 99%
“…From 2021 onwards, we identified 15 COVID-19-related studies [88,101,112,125,128,137,181,189,195,202,209,213,215,216,244]. These ranged from descriptive studies on disparities due to social determinants of health, the association of the virus with other conditions, severity in specific groups, provision of virtual care, treatment options, and changes in physician behavior.…”
Section: Current State and Opportunitiesmentioning
confidence: 99%